ChemInform Abstract: Crystal Structure of SrGeO3 in the High‐Pressure Perovskite‐Type Phase. Issue 30 (July 2015) - Nakatsuka, Akihiko; Arima, Hiroshi; Ohtaka, Osamu; Fujiwara, Keiko; Yoshiasa, Akira
Abstract Single crystals of the SrGeO3 high‐pressure phase are prepared by hot pressing of the polycrystalline pseudowollastonite SrGeO3 (BN anvil press, 6 GPa, 1223 K, 1 h).